Diagnostic certainty of idiopathic pulmonary fibrosis/usual interstitial pneumonia: The effect of the integrated clinico-radiological assessment. Issue 12 (December 2015) - Tominaga, Junya; Sakai, Fumikazu; Johkoh, Takeshi; Noma, Satoshi; Akira, Masanori; Fujimoto, Kiminori; Colby, Thomas V.; Ogura, Takashi; Inoue, Yoshikazu; Taniguchi, Hiroyuki; Homma, Sakae; Taguchi, Yoshio; et al.
Highlights: IPF/UIP cases were re-evaluated by expert chest radiologists and pulmonologists. Forty-one percent of cases were judged to be unlikely as IPF/UIP. Alternative diagnoses were listed: chronic hypersensitivity pneumonitis. Interstitial pneumonia associated with connective tissue disease. Idiopathic nonspecific interstitial pneumonia. Abstract: Objective: To reevaluate idiopathic pulmonary fibrosis (IPF) cases which had surgical lung biopsy (SLB) for diagnosis of usual interstitial pneumonia (UIP), and examine the influence of computed tomography (CT) findings and clinical information based on diagnostic certainty. Methods: Ninety-five cases with multidisciplinary diagnoses of IPF were identified from eight institutions. All cases had SLB. Two expert chest radiologists and five expert pulmonologists used a 5-point scale to grade their level of certainty in the diagnosis of a radiological pattern of UIP or a clinical diagnosis of IPF (level 1 "definitely no" to level 5 "definitely yes"). Radiologists independently evaluated thin-section CT images and pulmonologists independently assessed clinical information. The two groups then discussed their diagnosis to obtain a final consensus, and listed alternative diagnoses. Changes in the level of certainty during the diagnostic process were investigated. Results: The level of certainty for IPF was judged as low (level 1 or 2) in 32 cases (34%) by radiologists and in three cases (3%) by pulmonologists; in the final consensus 39 cases (41%) were judged as low. Chronic hypersensitivity pneumonitis (CHP), interstitial pneumonia associated with collagen tissue diseases (CTD-IP), and idiopathic nonspecific interstitial pneumonia (idiopathic NSIP) were listed as alternative diagnoses. Conclusions: In this retrospective series, some cases that had UIP confirmed on SLB for IPF diagnosis were classified into a low-level certainty group by expert chest radiologists and pulmonologists. When a diagnosis of IPF is made, the possibility of CHP, CTD-IP, and idiopathic NSIP must be also considered.